FINANCIAL RATIOS AND FINANCIAL DISTRESS IN RETAIL TRADE SECTOR COMPANIES - Hendro Sasongko; Agung Fajar Ilmiyono; Annisa Tiaranti (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2021)
Abstract: The purpose of this study is to examine and explain the effect of the current ratio, return on asset, debt to asset ratio, and total assets turnover to financial distress in the retail trade sub sector for the 2015-2018 period both partially and simultaneously. The research population is all retail trade sector companies listed in Indonesia Stock Exchange (IDX). Sample was selected using the purposive sampling method. The method of data analysis in the form of a quantitative analysis using multiple regression analysis. The results of the study revealed that partially the CR does not affect financial distress while the return on assets, debt to assets ratio and total assets turnover in partial effect on financial distress. Simultaneously, the CR, ROA, DAR and TATO affect the financial distress. This can be a concern for companies to pay more attention to these four elements so that companies avoid financial distress conditions as well as for investors who want to invest.Abstrak: Tujuan dari penelitian ini adalah untuk menguji dan menjelaskan pengaruh current ratio, return on assets, debt to asset ratio, dan total assets turnover terhadap financial distress pada subsektor perdagangan eceran periode 2015-2018 baik secara parsial maupun simultan. Populasi penelitian ini adalah seluruh perusahaan sektor perdagangan eceran yang terdaftar di Bursa Efek Indonesia (BEI). Sampel dipilih dengan menggunakan metode purposive sampling. Metode analisis data berupa analisis kuantitatif dengan menggunakan analisis regresi berganda. Hasil penelitian mengungkapkan bahwa secara parsial CR tidak berpengaruh terhadap financial distress sedangkan return on assets, debt to assets ratio dan total assets turnover secara parsial berpengaruh terhadap financial distress. Secara simultan CR, ROA, DAR dan TATO berpengaruh terhadap financial distress. Hal ini dapat menjadi perhatian bagi perusahaan untuk lebih memperhatikan keempat unsur tersebut agar perusahaan terhindar dari kondisi financial distress serta bagi investor yang ingin berinvestasi.